Age-Dependent Up-Regulation of HCN Channels in Spiral Ganglion Neurons Coincide With Hearing Loss in Mice - Shen, Haitao; Liu, Weilin; Geng, Qiaowei; Li, Hongchen; Lu, Mingshun; Liang, Peng; Zhang, Bo; Yamoah, Ebenezer N.; Lv, Ping (Frontiers in Aging Neuroscience, 2018)
Age-related hearing loss (AHL) is the most common sensory disorder in the elderly population, and the etiologies are diverse. To understand the underlying mechanisms of AHL, one strategy is to identify correlates of the disease for comprehensive evaluation of treatment approaches. Dysfunction and degeneration of spiral ganglion neurons (SGNs) are major contributors to AHL. Previously, we showed that one of the changes in the aging auditory system is SGN excitability increase in mice. Since hyperpolarization-activated cyclic nucleotide-gated (HCN) channels play important roles in determining neuronal excitability, we predicted that HCN channels in SGNs are involved in AHL. To investigate the contribution of HCN channels to AHL, we examined the expression and biophysical properties of HCN channels in SGNs from adult (2–3 months) and 11–12-month-old mice. We report a dramatic increase of HCN channel current (Ih) in SGNs in old mice (11–12 months old). The results matched well with increased expression of HCN1 and HCN2 subunits, suggesting that upregulation of HCN channels in SGNs is one of the important facets of the aging SGNs. Moreover, the activity of Ih produced a major impact on the firing properties of SGNs in older mice. The upregulation of Ih may contribute to AHL by regulating SGN excitability. We assessed whether increased SGNs excitability dovetail with neurodegeneration. Apoptosis-inducing factor (AIF)-mediated apoptosis in SGNs was observed in old mice and activation of HCN channels mediates AIF activation. Thus, these findings demonstrate stark correlation between age-dependent increased expression of HCN channels and Ih, and apoptosis in SGNs, which may contribute towards the varied mechanisms of AHL.